Prevalence and antimicrobial susceptibility of Listeria monocytogenes on chicken carcasses in Bandung, Indonesia - Yoni Darmawan Sugiri (2018)
This study was conducted to determine the prevalence and quantify the number of Listeria monocytogenes in fresh chicken carcasses sold in traditional markets and supermarkets in Bandung, West Java, Indonesia, and to determine the antimicrobial resistance patterns of the isolated L. monocytogenes strains. The overall prevalence of L. monocytogenes in chicken carcasses was 15.8% (29/184). When comparing samples from traditional markets and supermarkets, no significant difference in the L. monocytogenes prevalence was detectable (15.2 versus 16.3%). Of the samples, 97.3% had L. monocytogenes counts ,100 CFU/g, 2.2% had L. monocytogenes counts between 101 and 1,000 CFU/g, and 0.5% had L. monocytogenes counts of 1,001 to 10,000 CFU/g. Of the isolates, 27.6% were resistant to at least one of the 10 antimicrobials tested, with the major resistant phenotypes to penicillin (17.2%), ampicillin (6.9%), and erythromycin (6.9%). All 29 isolates recovered in this study were grouped into the molecular serogroup IIb, comprising the serovars 1/2b, 3b, and 7. Copyright ©, International Association for Food Protection.